Significance of long non-coding RNA IFNG-AS1 in the progression and clinical prognosis in colon adenocarcinoma. Issue 2 (20th December 2021) - Wang, Zhaoshun; Cao, Zhongzheng; Wang, Zhen
ABSTRACT: Colon adenocarcinoma originates from adenoma and triggers serious healthy burdensome. lncRNAs develop a crucial role in the progression of colorectal carcinoma. In this study, we aimed to investigate the clinical value and potential role of lncRNA interferon (IFN) gamma antisense RNA 1 (IFNG-AS1) in colon adenocarcinoma. This study enrolled 95 colorectal adenoma patients, 128 colorectal adenocarcinoma patients, and 88 healthy individuals. The serum, tissue IFNG-AS1 expression levels were explored by real-time quantitative reverse transcription-PCR (RT-qPCR) assay. The receiver operator characteristic curve and Kaplan-Meier method were used to assess the clinical significance of IFNG-AS1. The chi-square test was used to analyze the association between tissue IFNG-AS1 and clinical characteristics. Functional experiments were conducted to delve into the effects of IFNG-AS1 on cellular activities (cell viability/migration/invasion). The target miRNA of IFNG-AS1 was also explored. IFNG-AS1 expression in both serum and tissue samples was elevated in patients. Serum IFNG-AS1 could diagnose colon adenoma and adenocarcinoma patients from the healthy control. High tissue IFNG-AS1 was correlated with several clinical characteristics and a shorter overall survival time. Silence of IFNG-AS1 could be available for repressing cellular capacities via the sponge to miR-627-3p. IFNG-AS1 was rised in colon adenocarcinoma and it was relevant to tumor size, TNM stage, and poor prognosis of patients. Beyond that, downregulated expression of IFNG-AS1 may repress malignant progression of colon adenocarcinoma by regulating miR-627-3p. IFNG-AS1 might be a potential diagnosis or prognosis predictor for colon adenocarcinoma patients.